The effects of different silage additives on the quality of sugar beet pulp silage - Şahin, Kazım; Çerçi, IH; Güler, T; Şahin, Nurhan; Kalander, H; Çelik, S (Scientific Technical Research Council Turkey, 1999)
in this study, the effect of different silage additive added during ensiling period was investigated on the silages quality and determination of storage characters of sugar beet pulp. Treatment groups consisted of silage additives. These groups were K group no additives, F group with %5 formic acid, P group with %8 whole crop barley after wilting silage, M group with %8 corn silage and S group with whole crop barley added straw with treated HCl silage. The changes in nutrients contents, fermentation products, in vitro digestibility of dry matter, counts of mold and aerob bacteria of silage after silos opened and fresh material on days 0, 7, 14, 21, 28 and 36 were determined. Dry matter, crude protein, ether extract and crude fiber levels increased in silage groups as compared with fresh materials. However, nitrogen free extract contents decreased. Dry matter and nitrogen free extract contents were not different in treatment groups, but, the lowest values were determined in K group (p<0.05). The lowest pH was detected in F group, this group followed by S, P, M and K groups (p<0.01). Lactic acid concentration was high in M group but, lowest value was in F group (p<0.01). The highest acetic acid and ammonia -N were in K group. The differences were significant between K and treatment groups. While, butyric acid was detected in K group, but not in treatment groups. The in vitro digestibility of dry matter in silage was 61.12, 64.65, 63.89, 64.00 and 63.00% in K, F P, M and S groups, respectively (p<0.05). The highest counts of mold and aerob bacteria of sugar beet pulp and silage after silos opened on days 0, 7, 14, 21, 28 and 36 were in sugar beet pulp, this material followed by K and treatment groups. On the other hand, mold and aerob bacteria were not isolated in treatment groups after silos opened (0 d). The differences were significant between K and treatment groups.
Farkli Silaj Katki Maddelerinin Yaş Şeker Pancari Posasi Silaji Kalitesine Etkileri
Keywords: sugar beet pulp; additive; silage quality; bacteria; mold; digestibility